The pentapeptide Gly-Thr-Gly-Lys-Thr confers sensitivity to anti-cancer drugs by inhibition of CAGE binding to GSK3β and decreasing the expression of cyclinD1 - Kim, Youngmi (Oncotarget, 2017)
We previously reported the role of cancer/testis antigen CAGE in the response to anti-cancer drugs. CAGE increased the expression of cyclinD1, and pGSK3β(Ser9), an inactive GSK3β, while decreasing the expression of phospho-cyclinD1Thr(286). CAGE showed binding to GSK3β and the domain of CAGE (amino acids 231–300) necessary for binding to GSK3β and for the expression regulation of cyclinD1 was determined. (269)GTGKT(273) peptide, corresponding to the DEAD box helicase domain of CAGE, decreased the expression of cyclinD1 and pGSK3β(Ser9) while increasing the expression of phospho-cyclinD1(Thr286). GTGKT peptide showed the binding to CAGE and prevented CAGE from binding to GSK3β. GTGKT peptide changed the localization of CAGE and inhibited the binding of CAGE to the promoter sequences of cyclin D1. GTGKT peptide enhanced the apoptotic effects of anti-cancer drugs and decreased the migration, invasion, angiogenic, tumorigenic and metastatic potential of anti-cancer drug-resistant cancer cells. We found that Lys(272) of GTGKT peptide was necessary for conferring anti-cancer activity. Peptides corresponding to the DEAD box helicase domain of CAGE, such as AQTGTGKT, QTGTGKT and TGTGKT, also showed anti-cancer activity by preventing CAGE from binding to GSK3β. GTGKT peptide showed ex vivo tumor homing potential. Thus, peptides corresponding to the DEAD box helicase domain of CAGE can be developed as anti-cancer drugs in cancer patients expressing CAGE.